PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DI SD NEGERI 175799 BARUARA KECAMATAN BALIGE KABUPATEN TOBA - Sembiring, Polintan Rehulina; Mariani, Mariani; Sitepu, Cindy Sapika; Sembiring, Debby Tesalonika Br (Unversitas Katolik Santo Thomas, 2025)
This study aims to determine the effect of learning discipline on student learning outcomes in the Pancasila Education subject for grade V at SD Negeri 175799 Baruara, Balige District, Toba Regency. The research method used is the comparative method. The sample in this study amounted to 22 students. Data collection techniques were carried out through questionnaires, tests, and documentation. Based on the results of the hypothesis test, the t count value = 3.672 and t table = 2.164 were obtained. Because t count > t table (3.672 > 2.164), then H1 is accepted, which means that there is a significant influence between learning discipline and student learning outcomes. Thus, this study proves that learning discipline has a significant effect on the learning outcomes of Pancasila Education students for grade V at SD Negeri 175799 Baruara, Balige District, Toba Regency.